Spilanthol, the Principal Alkylamide from Acmella oleracea, Attenuates 5-Fluorouracil-Induced Intestinal Mucositis in Mice - de Freitas-Blanco, Veronica Santana; Monteiro, Karin Maia; de Oliveira, Patrícia Rosa; de Oliveira, Ellen Cristina Souza; de Oliveira Braga, Lucia Elaine; de Carvalho, João Ernesto; Ferreira Rodrigues, Rodney Alexandre (Planta Medica, 2019)
Mucositis is one of the commonest side effects in cancer patients undergoing treatment with radiotherapy and/or chemotherapy, and it currently lacks appropriate and effective treatment. Acmella oleracea, a species of flowering herb from South America, contains spilanthol, an alkylamide that has several pharmacological properties, including anesthetic, analgesic, and anti-inflammatory activities. Therefore, the purpose of this work was to evaluate the effect of spilanthol in intestinal mucositis in Swiss mice induced by 5-fluorouracil (5-FU), an antineoplastic agent administered systemically for the treatment of many different cancers. The repeated administration of 5-FU resulted in intestinal mucositis and consequent decreased food intake, together with weight loss, in all the animals. Daily administration of spilanthol significantly lowered the severity of intestinal mucositis, reducing histopathological changes and increasing the villus height in the animals treated with spilanthol at a dosage of 30 mg/kg (p < 0.0044) compared to a group exposed only to 5-FU. A decrease of myeloperoxidase activity was also observed in the animals treated with 30 mg/kg of spilanthol (p < 0.05), although several pro-inflammatory cytokines were not quantifiable in any group. In conclusion, the data demonstrated that spilanthol effectively reduced inflammation in a mouse model of intestinal mucositis induced by 5-FU, and that the compound might be a promising therapeutic candidate for the prevention and treatment of this condition.
Keywords: spilanthol; Acmella oleracea; Compositae; intestinal mucositis; 5-fluorouracil; chemotherapy